NAIP/NLRC4 inflammasome activation in MRP8+ cells is sufficient to cause systemic inflammatory disease - Randilea D. Nichols (Nature Portfolio, 2017)
Inflammasomes are protein complexes induced by pathogens for the secretion of pro-inflammatory cytokines IL-1β and IL-18 in immune cells. Here the authors show, using a new mouse model, that aberrant NLRC4 and ASC-dependent inflammasome activation in neutrophils contributes to systemic inflammation.